Crude Oil New Technologies and Recent Approaches - Elsayed Abdel-Raouf, Manar; Hasan El-Keshawy, Mohamed (IntechOpen, 2022)
Petroleum crude oil is the main energy source worldwide. However, global fossil fuel resources and reservoirs are rapidly and disturbingly being depleted. Thus, it is particularly important to shed light on new techniques developed for economic production and better utilization of crude oil. In addition, the processes involved in the production, refining, and transportation of crude oil are environmentally hazardous. It is essential to develop cleaner technologies and to find innovative solutions to overcome these problems. Over four sections, this book discusses materials used in cracking crude oil and improving its specifications, methods for reducing or eliminating the hazardous effects of petroleum pollution, and the environmental effects of crude oil, as well as presents case studies from different countries.